2016
DOI: 10.1177/0959683616640040
|View full text |Cite
|
Sign up to set email alerts
|

Deltaic land subsidence and sea level fluctuations along the east coast of India since 8 ka: A palynological study

Abstract: The consequences of climate change and land subsidence are often related to sea level rise/fall. Mangrove extinction and migration were assessed through palynological studies in two sedimentary cores in order to address climate, Relative Sea level (RSL) and its relation to geomorphology since 8420 cal. yr BP from Kanuru (500 cm deep) and since 5850 cal. yr BP from Machilipatnam (118 cm deep), Krishna delta, India. Four units/nine phases of sediment depositional environment were identified on the basis of marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Presence of high percentage of back mangroves such as Excoecaria agallocha , Avicennia sp. (salt tolerant mangrove) along with the foraminiferal lining indicates marine influence at the site (Farooqui and Nautiyal, 2016). Humidity and heavy precipitation can be inferred from the occurrence of fungal spores along with pollen of terrestrial vegetation (Medeanic et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of high percentage of back mangroves such as Excoecaria agallocha , Avicennia sp. (salt tolerant mangrove) along with the foraminiferal lining indicates marine influence at the site (Farooqui and Nautiyal, 2016). Humidity and heavy precipitation can be inferred from the occurrence of fungal spores along with pollen of terrestrial vegetation (Medeanic et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as the eastern margin of Indian subcontinent is tectonically stable, thus the change in its landscape and sediment delivered to the coastal basins located at this margin are the effect of long-term climatic fluctuations (Dash et al, 2020; Vaidyanadhan and Ghosh, 1993). Many multi-proxy studies have been carried out to unravel these long-term climatic fluctuations in the coastal regions of India (Farooqui and Nautiyal, 2016; Rao et al, 2015, 2020; Shah et al, 2022; Srivastava and Farooqui, 2013). Since the Neolithic period (2300–2100 BCE), the eastern part of Odisha has given shelter to early humans (Pradhan, 2005; Tripati and Vora, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Kumar, et al Later transgressive events recoded between 2970±100YBP and c. 3400 YBP along the eastern coast and northern South China Sea [71]. The coastal transformations were recorded due to major transgressive event, Farooqui et al, [72] have reported sea-level regression following the major transgressive event at 3150 BCE to 2370 BCE which transformed the geomorphology of the Chilika, Kolleru and even Pulicat Lagoon in AP (Andhra Pradesh) [73,74]. A drop in regional sea level points during the Little Ice Age (LIA) (300-250YBP) (Fig 7).…”
Section: Changes In Rslrmentioning
confidence: 99%
“…Palynological studies reveal that salt tolerant Mangroves resistant to saline atmosphere were extending from Kanuru, and Machlipatnam coast until Myanmar coast including Chilika coast during mid Holocene [54], Farooqui et al, [72].…”
Section: Mangrove Vegetationmentioning
confidence: 99%
“…temperature, precipitation, salinity), research on both local and regional scales is necessary to determine the potential impact of climate change on mangroves (Spalding et al 2010). Many studies have been conducted to understand the response of mangroves to Holocene climate and sea level changes worldwide (Ellison 1989; Parkinson et al 1994; Behling et al 2001; Li et al 2012; Limaye et al 2014; Farooqui et al 2016; Hait and Behling 2019; Rao et al 2020).…”
Section: Introductionmentioning
confidence: 99%